Effect of process parameters on microstructures and properties of Al–42Si alloy fabricated by selective laser melting. Issue 6 (June 2022) - Cai, Xiaoye; Liu, Tong; Yan, Xuan; Cheng, Zonghui; Pan, Lu; Tian, Zongjun; Luo, Liangshun; Su, Yanqing
Abstract: In this paper, high-silicon Al–42Si alloy was prepared by selective laser melting (SLM) with different process parameters. Microstructures evolution and defects formation were studied and process parameters were optimized. The results shown that the density of SLM-fabricated Al–42Si alloy increases as input energy density increases. The highest and lowest density of SLM-fabricated Al–42Si alloy are obtained, when input energy density is 42.9J/mm 3 and 33.8J/mm 3 respectively. The microstructures of Al–42Si alloy fabricated by selective laser melting is mainly composed of primary silicon phase and eutectic silicon phase, which is distinct from casting alloy because of diffient grains size and shapes of the primary silicon. With higher energy density, larger size of the primary silicon observed during process due to higher heat released by powder. The size of primary silicon phase particles is in the range of 2.9–9.4μm, and the size of molten pool during SLM process is in the range of 125 ± 10μm–140 ± 10μm in this study. Also the hardness of SLM-fabricated Al–42Si alloy increases as input energy density increases between 40.0J/mm 3 and 42.9J/mm 3 . After heat treatment, the residual stress is eliminated, microstructure stability and homogeneous of SLM-fabricated Al–42Si alloy are improved. The silicon distribution is more uniform and sizes increases about 1∼2μm, and the hardness decreases after heat treatment. The optimal SLM parameters for Al–42Si alloy are laser power of 320W, scanning speed of 1355 mm/s, layer thickness of 50μm and scanning space of 110μm. Abstract : Al-42Si alloy; Selective laser melting; Process parameters; Microstructures.